Implementation of Phenomenological Studies in Education: A Literature Study - Ediyanto, Ediyanto; Jatiningsiwi, Tata Gading; Hastuti, Wiwik Dwi; Novianti, Ranti (Proceeding of International Conference on Special Education in South East Asia Region, 2023)
Phenomenology is a science that discusses and reveals visible events or phenomena. The diversity of phenomenological research makes questions about phenomenological methods even more urgent. Several recent studies still overlap between phenomenological and case study research, where theoretically and practically, the two methods have different goals. This research aims to explore the current implementation of phenomenological methods through a literature review and examining crucial matters in phenomenological research. The Current study uses a systematic literature review method consisting of 3 stages: selection of the articles, analysis of studies, and categorization of the articles. The study results show that there were 20 previous studies reviewed. The implementation of the phenomenological method carried out in previous studies needs to follow the concept of phenomenology. In English language studies, 9 out of 10 studies provided study results according to the chosen method. Only one article was less suitable because it did not show the results of interviews that had been conducted. Then, in the Indonesian language study, 9 out of 10 did not show the results of the interviews that had been conducted. 7 out of 10 Indonesian language studies did not explain the sampling technique, and 2 out of 10 did not explain the participants in the study.